CADES and (Mathematics) Education in Brazil: Some Brief Remarks on the Books Edited by the Campaign for the Improvement and Diffusion of High School (1953-1971) Contribuições da CADES para a Educação (Matemática) Secundária no Brasil: uma Descrição da Produção Bibliográfica (1953-1971) - Ivete Maria Baraldi; Rosinéte Gaertner (Universidade Estadual Paulista, 2010)
The so called Campaign for the Improvement and Diffusion of High School (in Portuguese, CADES) took place between 1953 and 1971, in Brazil. During this period, the Campaign published or helped publish dozens of books, in different teaching areas, and several of them were located by the authors of this article. These books guided high school teachers with respect to curriculum planning, legal aspects and methods of teaching. In this article, we contextualize historically this Campaign and also mention its objectives. We briefly describe some of the books found - especially those related to the teaching of mathematics - in order to open perspectives for future approaches and research that can be done based on this written material. Our main aim is to discuss its orientations and to provide ingredients that enable the construction of considerations related to this perspective of training mathematics teachers during a period when there were few colleges and universities to prepare teachers in Brazil. Keywords: Brazilian High School Teaching. CADES. Publications. Mathematics Teachers. No Brasil, no período entre 1953 e 1971, é desenvolvida a Campanha de Aperfeiçoamento e Difusão do Ensino Secundário (CADES). Durante o período em que esteve em vigor, a Campanha publicou ou apoiou a publicação de dezenas de obras, em diversas áreas do ensino, sendo que muitas delas foram localizadas pelas autoras. Estas obras orientavam os professores do ensino secundário nos aspectos curriculares, legais e didáticos. Neste artigo, apresentamos uma contextualização histórica do que foi essa Campanha e de quais eram os seus objetivos, bem como a descrição de algumas das obras encontradas relacionadas com o ensino de matemática, buscando abrir caminhos para uma futura investigação mais profunda que auxilie a construção de considerações acerca dessa perspectiva de formação de professores de matemática, numa época em que, no Brasil, ainda existiam poucas faculdades ou universidades para formá-los. Palavras-chave: Ensino Secundário Brasileiro. CADES. Produção Bibliográfica. Ensino de Matemática.